已知3x平方-2x-3=0,则-3x平方+2x+5/6x平方-4x-1=
3个回答
解;由3x²-2x-3=0得:3x²-2x=3
所以:(-3x²+2x+5)/(6x²-4x-1)=[5-(3x²-2x)]/[2(3x²-2x)-1]=(5-3)/(2*3-1)=2/5
相关问题
急 已知3x平方-2x-3=0,则-3x平方+2x+5/6x平方-4x-1=
(1)X平方-x-3/4=0 (2) 3x平方+6x-5=0 (3)4X平方-X-9=0
(1)X平方2;+10X+16=0 (2)X平方2;-X-4分之3=0(3)3X平方2;+6X-5=0 (4)4X平方2
1、5(2+3t)的平方-3=0 2、x的平方+3=6x 3、x的平方+3x+1=0 4、4(x+1)的平方=9(x-3
已知5x的平方-3x-5=0,则5x的平方-2x-(1/5x的平方-2x-5)=
1,x的平方-2x-2=0 2,2x的平方+3x-1=0 3,2x的平方-4x+1=0 4,x的平方+6x+3=0
3M+N=4X平方-5X+3已知M=X 3的平方-X 2的平方+5X+6
计算:x平方+3x平方+2/1+x平方+5x+6/1+x平方+4x+3/1.
5x的平方+3x=0 x的平方+2x-3=5 (3x-2)的平方=(2x-3)的平方 3x的平方-10x+6=0
因式分解 x平方-2x+3 x平方-x+6 2x平方-3x+1 6x平方+5x-6